STRATEGI PEMBELAJARAN DHARMA GITA DALAM MENINGKATKAN NILAI-NILAI PENDIDIKAN KARAKTER HINDU DI PASRAMAN SWASTA PRANAWA - Eka Suci Arini; Ni Komang Wiasti; I Wayan Rudiarta (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2023)
The existence of the Regulation of the Minister of Religion of the Republic of Indonesia Number 56 of 2014 has an impact on the development of non-formal pasraman which stipulates that Hindu Religious Education is needed in order to form a Hindu community that has competence and knowledge, quality and competitiveness in the field of Hinduism. In this context, the role of pasraman is very important, especially in the field of educational development. This research focuses on two things, namely the learning strategy of Dharma Gita in increasing the values of Hindu character education and the obstacles encountered in implementing the learning strategy of Dharma Gita. The theory used to analyze the problems in this study is the theory of behaviorism by Albert Bandura and the theory of Humanism by Abraham Maslow. This research is a qualitative research with descriptive data presentation. Data collection was carried out using non-participant observation techniques, structured interviews and documentation studies. The data that has been collected is then analyzed through three steps, namely data reduction, data presentation, and drawing conclusions. Based on the research that has been done, the following results are obtained, 1) The Dharma Gita Learning Strategy is applied in learning at the Pasraman Swasta Pranawa, namely, using Cooperative Learning Strategies and Expository learning Strategies. 2) The obstacles encountered in implementing the Dharma Gita learning strategy are internal and external factors. Internal factors include 1) children have difficulty processing notes, 2) students lack focus in learning activities, and 3) low student motivation. External factors include factors from the community environment, in a community environment children learn about norms, rules and customs in society.Keywords: Learning, Strategies, Dharma Gita, Pasraman.